Detection and characterization of antibodies specific to food antigens (gliadin, ovalbumin and β-lactoglobulin) in human serum, saliva, colostrum and milk - Rumbo, Martín (1998)
Antibodies against food antigens are usually produced in healthy people. This humoral response can be detected both in serum and secretions. The characterization of this response can be useful for a better understanding of food-related immunological alterations. In this study, IgA and IgG antibodies specific to ovalbumin, β-lactoglobulin or gliadin were measured in serum, saliva, colostrum and milk from 40 healthy breast-feeding women. Specific IgA and IgG to the three antigens were measured by indirect ELISA. Specific IgG levels were highest in serum and very low in the other biological fluids. No correlation between the IgG specific to the different antigens was found. Specific IgA reactivity was found in all the samples analysed. Levels observed were higher in colostrum and milk than in serum and saliva. In spite of being three different unrelated food antigens, a correlation between the levels of specific IgA was found in saliva, colostrum and milk samples of all subjects studied. The specificity of IgA anti-gliadin antibodies from serum, saliva and colostrum was analysed by immunoblotting of SDS–PAGE-separated wheat proteins. Each sample presented a unique pattern of recognition. No common pattern of recognition was found either among the same biological fluids of the different subjects tested, or among the different samples—either serum, colostrum or saliva—of the same individual. Different degrees of specificity to wheat proteins among IgA from colostrum, saliva or serum were observed, suggesting that the local IgA-producing populations are functionally different in the different tissues of the organism.